It matters how much you talk: on the automaticity of affective connotations of first and second language words - Degner, Juliane; Doycheva, Cveta; Wentura, Dirk (Bilingualism, 2012)
We report the results of an affective priming study conducted with proﬁcient sequential German and French bilinguals to assess automatic affective word processing in L1 and L2. Additionally, a semantic priming task was conducted in both languages. Whereas semantic priming effects occurred in L1 and L2, and signiﬁcant affective priming effects were found in L1, affective priming effects in L2 were only found for participants with high levels of language immersion and frequency of L2 use. These results suggest that for sequential bilinguals the intensity of L2 use largely determines whether emotional words in L2 automatically activate their affective connotations.